2023
DOI: 10.1001/jamanetworkopen.2023.0010
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the ONKOTEV Risk Prediction Model for Venous Thromboembolism in Outpatients With Cancer

Abstract: ImportanceThe assessment of the risk of venous thromboembolism (VTE) among outpatients with cancer represents an unsolved topic. Current international guidelines recommend primary prophylaxis for patients at intermediate to high risk of VTE, indicated by a Khorana score of 2 or more. A previous prospective study developed the ONKOTEV score, a 4-variable risk assessment model (RAM) consisting of a Khorana score of more than 2, metastatic disease, vascular or lymphatic compression, and previous VTE event.Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The mean/SD summary estimates from the Cox prediction model were 0.479/0.253. We performed DCA/gDCA using ONKOTEV model ( n = 425) to assess its use as primary thromboprophylaxis in patients treated for cancer in the ambulatory setting 28 . The ONKOTEV employed competing‐risk time‐to‐event regression .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean/SD summary estimates from the Cox prediction model were 0.479/0.253. We performed DCA/gDCA using ONKOTEV model ( n = 425) to assess its use as primary thromboprophylaxis in patients treated for cancer in the ambulatory setting 28 . The ONKOTEV employed competing‐risk time‐to‐event regression .…”
Section: Methodsmentioning
confidence: 99%
“…We performed DCA/gDCA using ONKOTEV model (n = 425) to assess its use as primary thromboprophylaxis in patients treated for cancer in the ambulatory setting. 28 The ONKOTEV employed competing-risk time-to-event regression. Harell's C discrimination statistics was 0.71 for ONKOTEV with good calibration properties (with intercept and the slope not statistically significantly different from 0 to 1, respectively).…”
Section: Simulation and Comparison With Ipd-based Dcamentioning
confidence: 99%
“…In their prospective study, the area under the curve of ONKOTEV over the Khorana score was reported at 3 months (71.9% vs. 57.9%, p = 0.001), 6 months (75.4% vs. 58.6%, p < 0.001), and 12 months (69.8% vs. 58.3%, p = 0.014) [67]. Cella et al (2023) validated this model in the ONKOTEV-2, a multicenter prognostic study on ambulatory patients with solid tumors undergoing active treatments [68]. The most represented tumors were breast (18.1%), gastroesophageal adenocarcinoma (16.5%), colon (12.7%), lung (11.1%), rectum (10.8%), and pancreatic cancers (7.5%) [68].…”
Section: Vte Risk Assessment Using Scoresmentioning
confidence: 97%
“…Cella et al (2023) validated this model in the ONKOTEV-2, a multicenter prognostic study on ambulatory patients with solid tumors undergoing active treatments [68]. The most represented tumors were breast (18.1%), gastroesophageal adenocarcinoma (16.5%), colon (12.7%), lung (11.1%), rectum (10.8%), and pancreatic cancers (7.5%) [68]. Di Nisio et al reported that the performance of the Khorana, PROTECHT, CONKO, and ONKOTEV scores improved at the threshold of 2 points, compared to 3 points [49].…”
Section: Vte Risk Assessment Using Scoresmentioning
confidence: 99%
“…18 24 Furthermore, the ONKOTEV score, consisting of four variables: a Khorana score greater than 2, metastatic disease, vascular or lymphatic compression, and a prior history of VTE, was designed for ambulatory oncologic patients. 18 25 In the Tic-Onco risk score, clinical factors were incorporated in addition to a genetic risk score based on identified single nucleotide polymorphism risk alleles. 6 Another helpful model is the COMPASS-CT score, which includes various clinical characteristics and comorbidities, such as cardiovascular risk factors, treatment types (e.g., antihormonal therapy in hormone receptor-positive breast cancer), and platelet counts.…”
Section: Venous Thromboembolism and Bleeding Risk Assessment Scoresmentioning
confidence: 99%